Evidence for the Presence of RNA in the Purified Virions of Vaccinia Virus - Roening, G. (1974)
Vaccinia virus, strain WR, was propagated in HeLa cells, L mouse fibroblats, or primary chicken embryo fibroblasts in the presence of [5- (3)H]uridine. Carefully purified virions were found to contain significant amounts of labeled trichloroacetic acid-precipitable material which was rendered acid soluble when digested with pancreatic RNase or hydrolyzed in alkali. Controlled degradation of virions with Nonidet P-40 and 2-mercaptoethanol demonstrated that 65 to 80% of the [5- (3)H]uridine-labeled molecules resided in the viral core. When the total nucleic acids were extracted from viral cores prepared from virions propagated in HeLa cells, 30 to 50% of the total incorporated [5- (3)H]uridine was found in RNA; in L mouse fibroblasts, 40 to 50%; in primary chicken embryo fibroblasts, 50 to 60%. The RNA molecules do not appear to be covalently linked to the viral DNA genome but sediment in sodium dodecyl sulfate-sucrose gradients as 8 to 10S species relative to ribosomal RNA.